Biomass pyrolysis and catalytic upgrading of pyrolysis vapors for the production of fuels and chemicals / Masoud Asadieraghi - Masoud, Asadieraghi (2016)
The accurate determination of the biomass thermal properties is particularly important while studying biomass pyrolysis processes. The various palm oil biomass samples (palm kernel shell (PKS), empty fruit bunches (EFB) and palm mesocarp fibre (PMF)) thermochemical behavior was investigated during pyrolysis. To eliminate the negative impacts of inorganic constituents during biomass thermochemical processes, leaching method by different diluted acid solutions was chosen. The different palm oil biomass samples were pretreated by various diluted acid solutions (H2SO4, HClO4, HF, HNO3, HCl). Acids with the highest degrees of demineralization were selected to investigate the dematerialization impacts on the biomass thermal characteristics and physiochemical structure. Thermogravimetric analysis coupled with mass spectroscopy (TGA-MS) and Fourier transform infrared spectroscopy (TGA-FTIR) were employed to examine the biomass thermal degradation. TGA and DTG (Derivative thermogravimetry) indicated that the maximum degradation temperatures increased after acid pretreatment due to the minerals catalytic effects. Pyrolysis bio-oil from biomass comprised varieties of undesirable oxygenates and heavy compounds have to be treated. In-situ upgrading of bio-oil pyrolysis vapor is a promising approach demonstrating numerous benefits. Due to the highly complex nature of bio-oil, understanding the reaction pathways is highly desirable for catalyst and process screening. Therefore, the study of model compounds is the first step in simplifying the problem complexity to develop the fundamental processes and catalysts knowledge required to design bio-oil upgrading strategies. Three most important classes of catalysts including zeolites, mesoporous catalysts and metal based catalysts are mostly utilized for vapor phase bio-oil upgrading. The in-situ catalytic upgrading of PKS fast pyrolysis vapors was performed over each individual meso-H-ZSM-5, Ga/meso-HZSM-5 and Cu/SiO2 catalyst or a cascade system of iv them in a multi-zone fixed bed reactor. The catalysts were characterized using SEM, XRF, XRD, N2 adsorption and NH3-TPD methods. Furthermore, the produced bio-oils were analyzed using GC–MS, FTIR, CHNS/O elemental analyzer and Karl Fischer titration. Among different catalysts, meso-H-ZSM-5 zeolite demonstrated a very good activity in aromatization and deoxygenation during upgrading. The gallium incorporation into the meso-HZSM-5 zeolite increased the bio-oil yield and aromatics selectivity. A cascade system of catalysts comprising meso-HZSM-5, Ga (1.0 wt. %) /meso-HZSM-5 and Cu (5.0 wt. %) /SiO2 indicated the best performance on aromatics formation (15.05 wt. %) and bio-oil deoxygenation through small oxygenates, lignin derived phenolics and sugar derived compound conversion, respectively. Furthermore, catalytic upgrading of the PKS biomass pyrolysis vapor and its mixture with methanol were conducted in aforementioned fixed bed multi-zone reactor using HZSM-5 zeolite catalyst. The highly valuable chemicals production was a function of the hydrogen to carbon effective ratio (H/Ceff.) of the feed. This ratio was regulated by changing the relative amount of biomass and methanol. More aromatics (50.02 wt. %) and less coke deposition on the catalyst (1.3 wt. %) were yielded from the biomass, when methanol was co-fed to the catalytic pyrolysis process (H/Ceff. = 1.35). In this contribution, the deposited coke on the catalyst was profoundly investigated. The coke, with high contents of oxo-aromatics and aromatic compounds, was generated by polymerization of biomass lignin derived components.